Calcium signaling - Islam, Md. Shahidul (Advances in experimental medicine and biology, 2019)
This book covers topics ranging from fundamental aspects of calcium signaling to its clinical implications, in a thoughtful and comprehensive way. Includes discussion of calcium signaling in different mammalian cells, oocytes, Zebrafishes and even in plants.